Making the Global Local: Designing and Building a Mobile Studio to Research the Impact of Industry, Globalization, and Climate Change on Coastal Communities and Ecosystems (EAAE Joint Publishings, 2026)
This paper proposes a radical, multi-phase approach to architecture studio education that combines design-build, expeditionary learning, and analysis-based design research to embed students in the mobile study of the shipping industry, globalization, climate change, and their impacts on coastal communities and ecosystems. The modern shipping industry is the backbone of international trade, accounting for more than eighty percent of world trade, and its impact on the environment, coastal communities, and culture in general has become increasingly problematic. The model presented here proposes a series of interconnected courses, including design- build studios, history theory seminars, and research methodologies classes to allow students to form a comprehensive understanding of the core phenomenon while utilizing research and architectural production as a mode of inquiry. In the first phase begun in spring of 2023, students will design and build a mobile studio housed within a modified shipping container, sited temporarily on campus but designed to be periodically transported aboard an ocean-going cargo container ship. During concurrent and subsequent theory courses, students will establish research agendas focusing on links between the shipping industry and climate change, cultural globalization, and the economy while concentrating on the transformative effects it has on coastal communities and the environment. Students will engage in gathering data, mapping, marking, and making while searching for the intersection between architecture and the impacts of modern global trade on the world. The following paper includes a historical and contemporary analysis of the core issues, an assessment of the first stages of phase one begun in spring 2023 and makes a case for the value of design-build, expeditionary education, and the importance of travel, not just in learning, but in learning to employ architectural production to examine in-situ the most critical issues currently facing society and the environment.